AN EXAMINATION OF THE FACTORS INFLUENCING THE UTILIZATION OF SPAYLATER: ANALYSIS OF THE IMPACT OF LIFESTYLE, PROMOTION, AND CONVENIENCE, AND THEIR RELATIONSHIP TO THE CONCEPT OF TRUST - Putri Rayyan Tsaqila; Nurasia Nurasia; Putu Ari Oka; Fadilla Aisyah Aura (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2025)
The objective of this study is to ascertain the impact of lifestyle and promotional factors on the choice to utilize Spaylater as a payment method among Gen Z in Sumbawa City. Data were gathered through a questionnaire survey administered to 200 participants. A multiple linear regression model with a path analysis model was employed to analyze the data. The findings of this study indicate that lifestyle, promotion, and trust directly impact the decision to utilize Spaylater. Furthermore, the analysis revealed that lifestyle partially does not influence trust, while promotion affects user trust in Paylater. The indirect effect results demonstrate that lifestyle and promotion positively influence the decision to use Spaylater through trust as a mediating variable.